Passage‐dependent expression of STRO‐1 in human gingival mesenchymal stem cells. Issue 3 (27th September 2018) - Ranga Rao, Suresh; Subbarayan, Rajasekaran
Abstract: The expression of STRO‐1, the essential mesenchymal stem cell marker, was found to decrease with advancing passages in few tissues. Because STRO‐1 was identified and isolated from human gingiva, we were interested to know its status after a few passages. Human gingival mesenchymal stem cells (HGMSCs) were isolated from human gingiva. Flow cytometry was carried out with STRO‐1, mesenchymal stem cell (MSC) positive marker CD73, and negative marker CD34/CD45. Samples were also subjected to CD90 and STRO‐1 immunofluorescence staining. Gene expression was carried out for transcription factors OCT‐4, NANOG, and NESTIN. The results showed a gradual decrease in STRO‐1 and transcription factor expression with an increase in passage numbers. MSC positive marker CD73 was consistently expressed in all the passages. Negative markers were absent in all the passages. We conclude that STRO‐1 may be a useful marker to isolate undifferentiated (potent) mesenchymal cells from gingiva.